PROBLEMS RELATED TO THE INTERNATIONAL (STANDARD) STRATIGRAPHIC SCALE AND ITS PERFECTION - Zhamoida A.I. (My University, 2004)
All the aspects of the International stratigraphic scale (ISS) versions prepared by the International Commission on Stratigraphy in 2000 and 2002 are analyzed to show their similarity with and differences from the General stratigraphic scale (GSC) accepted and used in Russia. It is shown that the Precambrian ISS based on chronometric data is unacceptable, because geological systems of the Precambrian, except for the Vendian, cannot be defined. As is substantiated, the boundary and ISS stratotypes are complimentary, and the former can- not substitute the latter. The idea of validating the Phanerozoic ISS units depending on approval or rejection of the Global Boundary Stratotype Section and Point (GSSP) is criticized. It is shown that placing the Holocene and Pleistocene into the Neogene System, as it is done in the ISC-2002, we come to elimination of the autono- mous Quaternary System. The attitude of the Interdepartmental Stratigraphic Committee of Russia to the pro- cedure of consideration and acceptation of important international resolutions concerning general stratigraphic aspects is formulated. Substantiation of stratigraphic boundaries for stages established in Russia is supposed to be a procedure aimed at ISS perfection.